Representasi Pendewasaan Usia Perkawinan Iklan BKKBN “Yakin Siap Nikah?” di Channel Youtube Dalam Perspektif Semiotika - Syafruddin Pohan; Billy Betha Nagara; Sofya Rahma Nasution; Wanti Isadora Br Simbolon (LPPM Stikosa-AWS, 2023)
Abstract Child marriage is still a serious problem in Indonesia, prompting BKKBN to conduct a campaign for marriage-age maturity through an ad called